Cypriot nurses' knowledge of heart failure self-management principles - Kalogirou, Fotini; Middleton, Nicos; Sourtzi, Panayota A.; Lambrinou, Ekaterini (My University, 2013)
Background: The nurse's role as educator has become very crucial in heart failure management; thus, nurses must be adequately prepared to undertake this task. Aim: The main objective of the study was to estimate the level of Cypriot nurses' knowledge on basic heart failure self-care principles. Methods: A questionnaire measuring knowledge on heart failure self-care principles was administered among cardiology nurses working in five public urban hospitals of Cyprus. Data were analysed by using descriptive statistics, t-test and analysis of variance for categorical variables (such as gender and working setting) and correlation tests (Pearson's) plus simple linear regression for continuous variables (such as working experience). Results: Participants were 143 nurses. The mean heart failure self-care knowledge score was 13.57/20 (SD 2.33). Gender, hospital and cardiac clinical experience do not significantly affect scoring. Significant difference in the knowledge score was observed among critical care, cardiology and medical unit nurses (f=4.1, p=0.018). Post hoc analysis showed that this significant difference originated from the comparison of critical care nurses with cardiology unit nurses (14.1, SD 2.3 vs. 13.0, SD 2.1 respectively). Correlation and linear regression analyses yielded only weak negative correlation between correct scoring and duration of nursing practice (r=-0.262, p=0.002), with 6% of the total variation in scoring being explained by this relationship. Conclusions: Results are consistent with previous findings and it is thus under question whether cardiology nurses are properly educating their heart failure patients. Consequently, there is an urgent need for nurses to update their knowledge and enhance their educational skills.
Keywords: Heart failure; Nurses´ knowledge; Self-management